Understanding the Relative Roles of Salmon Spawner Enrichment and Disturbance: A High-Frequency, Multi-Habitat Field and Modeling Approach - Rüegg, Janine; Chaloner, Dominic T.; Ballantyne, Ford; Levi, Peter S.; Song, Chao; Tank, Jennifer L.; Tiegs, Scott D.; Lamberti, Gary A. (Frontiers in Ecology and Evolution, 2020)
Organisms exert multiple, often-contrasting, influences on ecosystems. Migrating Pacific salmon (Oncorhynchus spp.) deliver nutrients to freshwater ecosystems, but also disturb benthic sediments during upstream migration and nest building. The relative importance of these contrasting roles is not well understood, especially not in relation to the temporal dynamics of other environmental drivers. To assess the influence of salmon-mediated enrichment and disturbance, we measured stream biofilm metrics (production, respiration, chlorophyll a [chla], ash-free dry mass, stable isotope signatures) and environmental variables (spawner and carcass abundance, dissolved nutrients, temperature, discharge, light) from July through September in multiple habitats of a southeast Alaska stream. Biofilm production and biomass increased before and early in the salmon run, but declined later in the run. Biofilm stable isotope composition indicated incorporation of salmon-derived carbon and nitrogen (N) during the latter part of the run. Biofilm biomass differed among benthic habitat types (i.e., riffles, pools stream edges) but temporal patterns were generally similar, suggesting salmon and environmental influences were not habitat-specific. We used this high-frequency field data to parameterize an ordinary differential equation model for dissolved inorganic N, chla, and cellular N, and estimated model parameters using Marcov Chain Monte Carlo. Posterior distributions indicated that 1) habitats and locations were generally similar in model parameters, 2) removing the effect of salmon resulted in no change in biofilm chla early in the run (mid-August), but did show a decrease for some habitats later in the run (September), and 3) the overall integrated salmon effect over the run was one of biofilm loss. Only the combination of high frequency biofilm and environmental data collections with a process-based model, allowed us to determine how environmental context dynamics interact with salmon run dynamics to modulate the biofilm response in natal spawning streams. High-frequency field data combined with modeling provides a critical tool to gain a mechanistic understanding of resource subsidies, especially those from organisms that have other influences and roles, in relation to the environmental context and will allow us to evaluate the small and large scale importance of subsidies.